A comparative study of the effect of different polishing systems on ceramic dental surfaces - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
Although porcelain is the most esthetic restorative material available, it is subject to fracture during function. Glazing reduces the size of flaws in the surface of the porcelain and increases its resistance to crack propagation. The purpose of this study is to compare several polishing systems and the effects on the flexural strength of the ceramic material. 28 specimens were prepared from a feldsphatic body porcelain (Finesse(TM)-Dentsply Inc.) fabricated by sintering. These specimens were randomly divided into four groups. Whereas the specimens in the first group were glazed, those in the second were autoglazed and those in third and fourth groups were mechanically polished using different diamond polishing pastes. Surface roughness and 4-point bending tests were conducted on these specimens to determine the effects of using different polishing systems on dental ceramic surfaces. The glazed group displayed the highest flexural strength values and there were no statistically significant differences in the strength and the surface roughness values of the other three groups.
Keywords: polishing systems; surface roughness; flexural strength; feldsphatic porcelain; PORCELAIN; STRENGTH